Viability and Growth of Sugar Palm (Arenga pinnata (Wurmb.) Merr.) on Various Seed Maturity Levels Using Natural Soaking Solutions - Irwan Mahakam Lesmono Aji; Maiser Syaputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sugar palm (Arenga pinnata), a multi-purpose tree species (MPTS), has significant ecological and economic benefits. However, the imbalance between the benefits of this plant and its development is a concern. After reaching 50 years of age, the sugar palm tree can no longer reproduce, necessitating the need for cultivation. The primary challenge in cultivating this plant is its hard seed coat. While acidic ingredients have been used to break seed dormancy, natural ingredients are not commonly utilized. This study employed an experimental method with a completely randomized design (CRD). The study design included three factors: maturity level (K), soaking solution treatment (B), and soaking time (L). The parameters assessed in this study were maximum growth potential, germination capacity, leaf length, leaf area, number of leaves, stem diameter, stem length, primary root length, number of roots, and apical shoot length. The results indicate that soaking treatment did not significantly affect the parameters, except for root length. The maturity level treatment also did not significantly impact the parameters. However, K2 seeds (uniform yellow) showed better results in all parameters than other maturity levels, and B3 (100% coconut water) was the soaking solution that yielded positive results